2022
DOI: 10.3390/photonics9080553
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plasmonic Au and Ag/Au Nanoparticles and Sodium Citrate on the Optical Properties of Chitin-Based Photonic Nanoarchitectures in Butterfly Wing Scales

Abstract: Porous butterfly wings with hierarchically organized structures from nanometer to centimeter scales were tested as substrates for carrying plasmonic Au and Ag/Au nanoparticles with potential application in photocatalysis. Wings exhibiting structural color generated by chitin-air nanocomposites were used. Hundreds of butterfly species possess these types of color-generating photonic nanoarchitectures, producing color by a similar mechanism to manmade photonic crystals. Artificial photonic crystals are known to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…In our work focusing on Morpho butterflies, we were able to increase the catalytic efficiency of the butterfly wings covered by a conformal 20 nm thin layer of ZnO by about ten times as compared to a flat glass substrate [ 50 ]. Previous work on plasmonic Au nanoparticles and the photonic nanoarchitectures of male Polyommatus icarus wings showed that the Au nanoparticles incorporated into the photonic nanoarchitecture of the butterfly wings exhibited hybridization between the photonic nanoarchitecture and the metallic nanoparticles with plasmonic properties [ 57 ]. These findings strongly support our belief that combining photonic nanoarchitectures of biologic origin with various well established materials science methods may bring important advantages in a cheaper and more environmentally friendly way in several fields.…”
Section: Resultsmentioning
confidence: 99%
“…In our work focusing on Morpho butterflies, we were able to increase the catalytic efficiency of the butterfly wings covered by a conformal 20 nm thin layer of ZnO by about ten times as compared to a flat glass substrate [ 50 ]. Previous work on plasmonic Au nanoparticles and the photonic nanoarchitectures of male Polyommatus icarus wings showed that the Au nanoparticles incorporated into the photonic nanoarchitecture of the butterfly wings exhibited hybridization between the photonic nanoarchitecture and the metallic nanoparticles with plasmonic properties [ 57 ]. These findings strongly support our belief that combining photonic nanoarchitectures of biologic origin with various well established materials science methods may bring important advantages in a cheaper and more environmentally friendly way in several fields.…”
Section: Resultsmentioning
confidence: 99%